Histomorfometria das terminações nervosas das conchas nasais inferiores de humanos por imunofluorescência e microscopia confocal a laser - Peixoto, Magno Eric Barbosa (2017)
Nasal obstruction is one of the main complaint of patients with rhinitis, which is frequently associated with increased nasal airway resistance caused by hypertrophic changes of the inferior turbinates, however, studies have demonstrated that the objective measurement of nasal airway resistance does not always correlate with the subjective perception of the degree of nasal obstruction. The inferior turbinates are elongated, paired structures situated at the lateral nasal wall and made of a central core of osseous skeleton and a mucosal layer on each side almost exclusively covered with a pseudostratified ciliated columnar epithelium, with a well-defined basement membrane zone and a thick lamina propria. They play an important function in nasal physiology through reflex responses. The sensory nerves monitor the conditions of the mucosal microenvironment and initiate protective mechanisms immediately via axon responses. These nerve endings also have an important role on the perception of nasal patency. Despite the importance of these structures, little is known about their morphology and distribution in the normal nasal mucosa of human inferior turbinates. In order to obtain morphological and distribution data of nerve endings in inferior turbinates, specimens obtained from six individuals (three men and three women) with ages ranging from 16 to 76 years were submitted to fluorescent antibody technique with the marker pan -axonal anti-protein gene product 9.5 and confocal laser scanning microscopy. Free nerve endings were identified, mainly in the superficial layers of the lamina propria, some very close to the basement membrane. No complex nerve endings of the corpuscular type were identified. There were no differences in the distribution of nerve endings when compared to the septal and meatal faces or according to the gender of the individuals evaluated. Free nerve endings maintain an intimate relationship with seromucous glands and their ducts in the more superficial layers of the lamina propria, as well as with blood vessels, especially in their deeper portions, pointing to the role they play in the neuromodulation of glandular secretion and vasomotor control. Surgical techniques that allow the preservation of these free nerve endings may provide better postoperative outcomes, with a higher resolution of the clinical complaint of nasal obstruction and a lower rate of complications such as empty nose syndrome.